Economic Development and Marketing Strategies: a Comparative Lens - Sarathy, Ravi; Banalieva, Elitsa R. (Organizations and Markets in Emerging Economies, 2014)
Go back We analyze two core models of economic development in emerging markets: socialism (i.e., the “visible hand” of the state in directing the country’s socio-economic life) and capitalism (i.e., the “invisible hand” of the markets implemented through pro-market reforms). We further distinguish between two types of socialist economic development: Soviet Communism (as experienced in the pre-1990s Central and Eastern European transition economies) and Fabian Socialism (as experienced in pre-1991 India). We then suggest that companies can adapt to the evolution from socialism to capitalism in their countries through the implementation of more sophisticated marketing strategies that can ensure a sustainable competitive advantage. Thus, we study the marketing strategies of companies from emerging markets operating under both models of economic development. We analyze the opportunities and challenges that emerging market companies face under each model of economic development in terms of deploying various marketing strategies, and provide useful venues for future research.